Searching for new fiscal rules in the euro area: a new proposal - Jan Priewe (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
While the European Union (EU) fiscal rules are suspended in the years 2020–2022, new rules are in the making and might be activated in 2023. If the old rules were used again, massive austerity would be required in the face of the strongly elevated level of public debt and the gap to the 60 per cent debt cap in the EU Treaty. A new proposal is suggested in this article which requires only small changes in the Treaty and/or the Fiscal Compact, but a strong overhaul in secondary law, that is, the Stability and Growth Pact. The key ideas are to use net interest payments, as a share of GDP, as the new metric for defining debt sustainability rather than gross public debt. This would allow the adjustment of the rules to changing monetary environments, especially interest-rate levels, and changing differentials between interest rates and growth rates. This way, much more fiscal space would be generated both for higher-debt and lower-debt member states and the entire euro area.
Keywords: E43; E62; H62; H6; 330; fiscal policy; Stability and Growth Pact; public debt; fiscal deficits; monetary union; debt sustainability